The nurse and the nursing record in a public educational hospital - Karilena Karlla de Amorim Pedrosa; Marília Fernandes Gonzaga de Souza; Akemi Iwata Monteiro (Rev Rene)
Nursing records in the patient’s medical register are, even today, a problem observed in hospitals. Our aim in this research was to characterize the records made by nurses and demonstrate the information they have given. This is a descriptive, exploratory qualitative approach held in a Public Educational Hospital in Natal/ RN- Brazil, covering 30%(23) of the records of July/2009, who were in process of invoicing, archiving and recording and of which they found records. Of those, 16(70%) had some kind of registration of nurses, such as leaf development, admission to the Surgical Center, high, and only 1 (4%) had records relating to nursing care. Extending the analysis to the quality of records, he noted that 7 (30%) were readable and 15(65%) had signed, but there wasn’t either identification of the professional category, or the inscription of the Board of Nursing, making it difficult the distinction of who was the nurse or practical nurse. There are records made by the devaluation of nursing, which contributes to its own invisibility.